PENGARUH PENYULUHAN MAKANAN BERGIZI BERAGAM SEIMBANG DAN AMAN DENGAN MENGGUNAKAN FLASH CARD DALAM MENINGKATKAN PENGETAHUAN DAN SIKAP ANAK KELAS 1 – 3 SD ISLAM TITI BERDIKARI KECAMATAN MEDAN LABUHAN TAHUN 2014 - Syofia .; Albiner Siagian; Ernawati Nasution (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
The high rates of malnutrition and over nutrition in primary school students require serious handling. Giving information about various nutritional balanced and secure foods is to increase knowledge and attitude of students to choose the various nutritional balanced and secure foods in their everyday menus. The research’s purpose was to find out the influence of counceling on knowledge and attitude of students in Titi Berdikari Primary School of Medan Labuhan in 2014. The study was quasi experiment with one group pretest and posttest design. There were 80 students of population and 67 students of sample. Treatment was counseling in lecture method and gaming with flash cards. Measurements were taken twice, before and after getting counseling. Result was analyzed by paired t-test with confidence interval 95%. Result showed that the students’ knowledge increased from bad category (67,2%) to adequate category (94,0%). The students’ attitude increased from adequate category (70,2%) to good category (76,1%). The test results showed there were different score of knowledge and attitude after the counseling (p=0,000). The conclusion is the counseling with flash card has an influence on improving students’ knowledge and attitude about various nutritional balanced and secure foods, it is proved by the improvements of students’ knowledge and attitude about it. The suggestion is given to the local health department to pay more attention about nutrition counseling in school; and to the nutrition department in public health center and school to use the attractive-designed flash cards as a media for learning. Keywords: various nutritional balanced and secure foods; flash cards, primary school students